Distribution and spread of the invasive slug Arion vulgaris Moquin - Tandon in Norway - Hatteland, Bjørn Arild; Roth, Steffen; Andersen, Arild; Kaasa, Kristin; Støa, Bente; Solhøy, Torstein (Fauna norvegica, 2016)
The present distribution of the invasive slug Arion vulgaris Moquin-Tandon was studied in Norway. This important pest species has spread to many parts of Europe during the last decades, inflicting damage to agriculture and domestic gardens. It was first recorded in Norway in 1988, and has since spread to many parts of the country and is now recorded in 192 municipalities. We surveyed the current distribution by sampling and gathering species records in cooperation with garden societies and local authorities. Based on these records, we present distributional data as well as relative predictions of future distributions based on geoclimatic parameters. Currently, A. vulgaris covers most of coastal southern Norway while it shows a patchy distribution in northern Norway, recorded as far north as Finnsnes in Troms County. publishedVersion